Ozonization, Amination and Photoreduction of Graphene Oxide for Triiodide Reduction Reaction: An Experimental and Theoretical Study. (1st February 2017) - Jing, Hongyu; Ren, Suzhen; Shi, Yantao; Song, Xuedan; Yang, Ying; Guo, Yanan; An, Yonglin; Hao, Ce
Abstract: This work proposes a mild and environmentally-friendly approach to prepare a highly efficient functional graphene (termed as AGO-hv) using methods of ozone oxidation, solvothermal synthesis, and photoreduction. The use of ozone oxidation in the first step can effectively increase the interlaminar distance between graphite oxide sheets, and create active sites for nucleophilic attack on the epoxy carbon from ammonia. The amino groups were successfully grafted on the surface of graphene as evidenced by the amidation reaction, with a maximum nitrogen content of 10.46 wt% and a C/N molar ratio of 8.46. After further photoreduction of the aminated graphite oxide (AGO), the residual oxygen functionalities, such as C-OH, were effectively removed and the conductivity of the graphene sheet was further recovered. The dye-sensitized solar cell (DSC) exhibited a power conversion efficiency (PCE) of 7.51% based on AGO-hv counter electrode (CE), close to that of Pt counterpart (7.79%). The experimental results indicated that the amidation and photoreduction processes were significantly facilitated by the initial ozonization of graphene oxide, and this process significantly improved the electrochemical activity and the conductivity of graphene oxide. Density functional theory (DFT) calculations revealed that AGO-hv had the lowest ionization energy (a better electron-donating ability) and also suitable binding energy with I atoms as well. The combination of ozonization, amination and photoreduction is an efficient route to obtain electrocatalysts with desired compositional distributions and performance for triiodide reduction reaction in DSCs.